Efflux ABC transporters in drug disposition and their posttranscriptional gene regulation by microRNAs - Wang, Yimei; Tu, Mei-Juan; Yu, Ai-Ming (Frontiers in Pharmacology, 2024)
ATP-binding cassette (ABC) transporters are transmembrane proteins expressed commonly in metabolic and excretory organs to control xenobiotic or endobiotic disposition and maintain their homeostasis. Changes in ABC transporter expression may directly affect the pharmacokinetics of relevant drugs involving absorption, distribution, metabolism, and excretion (ADME) processes.Indeed, overexpression of efflux ABC transporters in cancer cells or bacteria limits drug exposure and causes therapeutic failure that is known as multidrug resistance (MDR). With the discovery of functional noncoding microRNAs (miRNAs) produced from the genome, many miRNAs have been revealed to govern posttranscriptional gene regulation of ABC transporters, which shall improve our understanding of complex mechanism behind the overexpression of ABC transporters linked to MDR. In this article, we first overview the expression and localization of important ABC transporters in human tissues and their clinical importance regarding ADME as well as MDR.Further, we summarize miRNA-controlled posttranscriptional gene regulation of ABC transporters and effects on ADME and MDR. Additionally, we discuss the development and utilization of novel bioengineered miRNA agents to modulate ABC transporter gene expression and subsequent influence on cellular drug accumulation and chemosensitivity. Findings on posttranscriptional gene regulation of ABC transporters shall not only improve our understanding of mechanisms behind variable ADME but also provide insight into developing new means towards rational and more effective pharmacotherapies.